Pergeseran Nilai Tradisional Tari Lulo Dalam Konteks Komunikasi Budaya Di Era Modern - Widya Rahmawati; Nasruddin Suyuti; Paramitha Purwita Sari (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study is based on the phenomenon of changes in the practice of the Lulo Dance, which was previously rich in social and cultural values but is now undergoing a shift due to the passage of time and the influence of globalization. The purpose of this study is to identify shifts in traditional values in the performance of the Lulo Dance and to analyze the factors influencing these shifts in Ambepulu Village, Tongauna Subdistrict, Konawe Regency. This study employs a qualitative approach using the case study method. Data collection techniques include observation, interviews, and documentation. The informants in this study consist of local community members involved in the performance of the Lulo Dance. Data were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that a shift in traditional values has occurred within the Lulo Dance, encompassing changes in the community’s values, attitudes, and behaviors. The Lulo Dance, which was once sacred and rich in cultural values, is now more oriented toward modern entertainment. This change is evident in the use of remixed music, changes in costumes, and a diminishing understanding of traditional values among the community.The factors influencing this shift include internal factors, such as changes in public mindset, as well as external factors, such as globalization, social media, and technological advancements. The conclusion of this study indicates that the shift in traditional values within the Lulo Dance represents an adaptation to the changing times; however, preservation efforts are still necessary to ensure that the cultural values it embodies are not lost.